2012
DOI: 10.1007/s10812-012-9564-8
|View full text |Cite
|
Sign up to set email alerts
|

Spectronephelometric methods to determine microphysical characteristics of dust in aspiration air and off-gases in cement plants

Abstract: The information value of spectral directional scattering coefficients of cement dust released into both the atmosphere and aspiration air during cement production is analyzed in terms of the concentration and effective dust particle size based on a regression approach to solving the inverse problem. The most effective layouts of dust meters that combine ease of implementation with high accuracy over the entire range of physicochemical properties of dust are considered.Introduction. The activity of cement plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Zvereva et al (2008) investigated the general pattern of changes in species richness and diversity of vascular plants due to environmental contamination, and associated habitat changes imposed by point polluters and identified the sources of variation in the response of plant communities to industrial pollution at a global scale. Lisenko et al (2012) suggested spectronephelometric methods to determine microphysical characteristics of dust in aspiration air and off-gases in cement plants. Edral and Demirtas.…”
Section: Introductionmentioning
confidence: 99%
“…Zvereva et al (2008) investigated the general pattern of changes in species richness and diversity of vascular plants due to environmental contamination, and associated habitat changes imposed by point polluters and identified the sources of variation in the response of plant communities to industrial pollution at a global scale. Lisenko et al (2012) suggested spectronephelometric methods to determine microphysical characteristics of dust in aspiration air and off-gases in cement plants. Edral and Demirtas.…”
Section: Introductionmentioning
confidence: 99%